Enhancing Students Reading Comprehension in Recount Text through Cooperative Learning Model of IX Grade SMP Negeri 1 Siantar - Juliana Tifani; Tiodor Sihotang; Sarah Lumbantobing; Ariel Jonivedi Silalahi; Dumaris E Silalahi (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
This research, entitled “Enhancing Students’ Reading Comprehension in Recount Textthrough Cooperative Learning Model (Jigsaw) of IX Grade SMP Negeri 1 Siantar,” aimed todetermine whether the Jigsaw technique could improve students’ comprehension of recounttexts. The problem of this study was based on the students’ difficulty in identifying mainideas, finding detailed information, and understanding the structure of recount texts. Toaddress this issue, the Cooperative Learning Model through the Jigsaw technique was appliedto encourage active participation and peer collaboration during the learning process. Thisstudy employed a descriptive quantitative design and involved 32 students of class IX-5 atSMP Negeri 1 Siantar in the academic year 2025/2026. The data were collected through areading comprehension test consisting of 20 multiple-choice questions conducted in onemeeting. The results showed that students’ comprehension improved significantly afterlearning through the Jigsaw technique. The total pre-test score was 1,970 with a mean of61.56 (Fair), and the post-test score increased to 2,560 with a mean of 80.00 (Good),showing an improvement of 30.02%. The findings indicate that the Jigsaw techniqueeffectively enhanced students’ ability to identify main ideas, recognize text organization, andinterpret vocabulary in context. Therefore, it can be concluded that the Cooperative LearningModel using the Jigsaw technique is an effective and engaging strategy for improvingstudents’ reading comprehension in recount textsKeyword : Jigsaw technique, cooperative learning, reading comprehension, recount text,junior high school